Cellulose From Water Hyacinth As Acrylamide Adsorbent In Frying Oil - Wulandari, Winda Trisna; Sugiharti, Mulya Tri; Wardani, Gatut Ari (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2024)
Cooking oil frequently used by the community is palm oil. When heated repeatedly, this oil can produce acrolein, a compound that contributes to the formation of acrylamide. Water Hyacinth cellulose contains -OH groups capable of binding to acrylamide. The purpose of this study was to determine the effect of adding Water Hyacinth cellulose as an adsorbent and to evaluate the impact of soaking time and cellulose weight on acrylamide levels. The analysis was conducted using HPLC, with a mobile phase consisting of methanol and 0.1% phosphoric in a ratio of 5:95, at a flow rate of 1mL/min; the volume of the injected sample was 20 µL. Acrylamide in oil was identified at a retention time of 4.700 minutes. The regression equation obtained from the acrylamide calibration curve is y=229.52 x + 10.472 with a correlation coefficient (R2) of 0.9988. This study concluded that soaking for 24 hours can reduce acrylamide levels by 69.13%, and using 6 grams of cellulose can reduce acrylamide levels by 75.15%.